MILITARY IN POLITICS AND NIGERIA’S POLITICAL EVOLUTION, 1966-1979 - OLUWASEYI PAUL ADEBILE; TOYYIBAT NIKE OGUNBONA (International Studies Journal)
Beginning from the sixties of the twentieth century, military ascendancy was a major feature that exerted masculinity on Nigeria’s political evolution. This accounted for the different experiences of military intervention and administration almost throughout the second half of the twentieth century. Essentially, the long-term impact of military governance in Nigeria’s socio-political and economic development trajectory warrants more critical analysis. In light of this, the paper explores the military in the Nigerian political landscape from 1966, when the first military coup took place, to 1979, which marks the end of its first phase, which was succeeded by the second Nigerian republic. The paper adopts the conventional historical method, relying on secondary sources for its exploration. The paper found out that beyond the usual alibi of civilian incompetence, socioeconomic underdevelopment, corruption as well as electoral crisis; insurgent tendencies arising from ethnic nationalities as well as secessionist agitation were central to military intervention and administration in Nigeria during the period under evaluation. The paper concludes with reflections on the vestiges of military intervention and administration on Nigeria’s civilian political culture and thereby recommends that attempts to address Nigeria’s contemporary political acrimonies must necessarily appreciate the historical context and experiences of the nation’s military governance, particularly between 1966 and 1979.